School of Love - Workout : A conversation with School of Love. - Grusenmeyer, Lauren (Antwerp : KDG/Sint Lucas, 2019)
Arda, Hazal ; Grusenmeyer, Lauren ; Hazarika, Ritam ; Langsdorf, Heike ; Mestre, Lilia ; Meul, Stef ; Vassalou, Elli ; Zakai, Adva ; Zalewska, Weronika
This publication is part of the research project Workout, founded by Lauren Grusenmeyer and done at Sint Lucas Antwerp. An investigation into the use of 'contraints' in visual arts and graphic design, or how the use of restrictions and time limits create freedom.
boek